2020
DOI: 10.1042/bsr20201313
|View full text |Cite|
|
Sign up to set email alerts
|

Circ_0000144 functions as a miR-623 sponge to enhance gastric cancer progression via up-regulating GPRC5A

Abstract: Background: Gastric cancer (GC) remains one of the most common malignancies worldwide. Increasing evidence has demonstrated that circRNAs serve as critical roles in human cancer, including GC. In the current study, we focused on the detailed function and mechanism of circ_0000144 on GC progression. Methods: The levels of circ_0000144, miR-623 and G protein-coupled receptor, family C, group 5, member A (GPRC5A) were determined by quantitative real-time polymerase chain reaction (qRT-PCR). Targeted relationships… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“… 27 In addition, hsa_circ_0000144 sponged miR-623 to upregulate GPRC5A expression, so as to promote GC progression. 28 In keeping with former discoveries, we also detected the upregulation of hsa_circ_0000144 in GC tissues and cells, especially in OXA-resistant tissues and cells. The inhibitory influence of hsa_circ_0000144 knockdown on OXA resistance, proliferation and metastasis in OXA-resistant GC cells in vitro, as well as on tumor growth in vivo was disclosed.…”
Section: Discussionsupporting
confidence: 88%
“… 27 In addition, hsa_circ_0000144 sponged miR-623 to upregulate GPRC5A expression, so as to promote GC progression. 28 In keeping with former discoveries, we also detected the upregulation of hsa_circ_0000144 in GC tissues and cells, especially in OXA-resistant tissues and cells. The inhibitory influence of hsa_circ_0000144 knockdown on OXA resistance, proliferation and metastasis in OXA-resistant GC cells in vitro, as well as on tumor growth in vivo was disclosed.…”
Section: Discussionsupporting
confidence: 88%
“…The downstream activation of YAP by hypoxia required GPRC5A, which enabled hypoxic cell survival by suppressing apoptosis via BCL-XL induction 40 . Studies in gastric cancer also suggested that GPRC5A was an oncogene exerting its function by regulating EMT or the epidermal growth factor receptor (EGFR) signaling 44 , 45 . Sawada et al reported that in prostate cancer GPRC5A facilitated cell proliferation through cell cycle regulation and was significantly essential for bone metastasis 46 .…”
Section: Discussionmentioning
confidence: 99%
“…Hsa_circ_0000144 was reported to promote GC cell proliferation, migration, and invasion [34]. Mi et al [35] demonstrated circ-0000144 knockdown could repress GC progression by regulating GPRC5A expression via sponging miR-623. Significantly aberrant expressed hsa_ circ_0000144 was identified in BC in current study, which had been confirmed with qRT-PCR as well.…”
Section: Discussionmentioning
confidence: 99%